Nesting features of the red squirrel (Sciurus vulgaris) in conditions of Kamianets-Podilskyi - Mykola Маtvieiev; Olena Buchatska (Theriologia Ukrainica, 2020)
Research on the biotopic distribution, abundance, and specific nesting features of the European red squirrel (Sciurus vulgaris)was carried out from October 2016 until May 2017 in the entire area of Kamianets-Podilskiy (Khmelnitskiy Oblast, Ukraine). By its construction type and tree vegetation, the following biotopes were singled out in the town area: one-storey buildings, multi-storey buildings, mixed housing types, parks, industrial area, the Smotrych river’s canyon, and gardening area. In total, 272 nests of the European red squirrel were registered, including 89 nests in parks (32.7 % of the total number of nests), 79 in the industrial area (29.0 %), 49 in the mixed housing area (18.0 %), 19 in the area of multi-storey buildings (7.0 %), 13 in the area of one-storey buildings (4.8 %), 12 in the gardening area (4.4 %), and 11 in the canyon of the Smotrych river (4.0 %). In Kamianets-Podilskiy and its surroundings, 178 178 pairs of the European red squirrel were recorded, what makes up 65.4 % of the number of registered nests. The population density (pair/km2) of the red squirrel in Kamianets-Podilskiy is 6.4 pairs/km2. The highest density was observed in the forest-park area (43.3 pairs/km2), in the canyon of the Smotrych river (10.7 pairs/km2), and in the area multi-storey buildings (9.1 pairs/km2). Squirrel nests were observed on 21 tree species, including the linden Тіlіа sp., the asp Populus sp., the chestnut Aesculus hippocastanum, the sycamore tree Acer tataricum, the field maple Асеr саmреstrе, the elm tree Ulmus laevis, the sweet cherry Prunus sp., the maple Acer negundo, the fir tree Рісеа sp., the walnut tree Juglans regia, the horn beech Саrріnus bеculus, the willow Salix alba, the acacia Robinia pseudoacacia, the ash tree Frахіnus ехсеlsіоr, the birch tree Betula sp., the poplar Populus sp., the pyramidal poplar Populus pyramidalis, the cedar Thuja occidentalis, the Norway maple Acer platanoides, the honey locust Gleditsia triacanthos, and the oak Quеrсus rоbur. Most nests were located on the pyramidal poplar (24.1 %), linden (19.7 %), and Norway maple (13.7 %), while the least number of nests was found on the fir tree (0.8 %) and chestnut (0.8 %). The European red squirrel usually arranges its nests at the height of 3.5 m to 23 m, in average 9.3 m. The specific features of location of squirrel nests depend on the tree species (the highest nests being located on the ash tree, pyramidal poplar, and the lowest nests being on the fir tree and cedar). The squirrel mostly arranges its nests at whorls usually made up of 3–4 branches (51.9 %), near the trunk (32.7 %), on the branches (13.0 %) and between trunks (2.4 %).